Batasan Dan Aspek-Aspek Agama Dalam Persepektif Sosiologi - Mawardi Mawardi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
In the sociological perspective, religion is not only doctrinal-ideology and abstract but also appears in the forms of materials in everyday life. Anthropologists and sociologist, for example, argue that the human phases from the Stone, Copper, and Bronze to the Iron Age where humans gathered food by hunting, farming, and industrialization influence their interpretation of religion. In the hunting period, they feared and trembled when seeing towering trees, large rocks, high and steep cliffs, and floods. Such fear and shock feelings caused dependency and in turn led them to plead for help by worshiping them. This article focuses on the sociological views of the definition, origin, and aspects of religion. Religion is understood as a social phenomenon embraced by a society and is viewed as a part of a culture. Religion and religious life are integral elements of the human life and cultural systems. Religion and religious behaviors grow and develop from the sense of human dependence on the supernatural power which they believe as the source of life. Thus, in the sociological perspective, there are some very important aspects in practicing the religion i.e., religious belief, religious ritual, religious experience, and religious community.